Bhajana Samskara: A Unique Method of Drug Fortification with Essential Metals (International Journal of Ayurveda and Pharma Research, 2023)
Samskara is a key drug formulation technique in which a formulation is altered based on the Prakriti of the person and disease. Many types of Samskara have been mentioned among them Bhajana samsakara the unique one where container plays an important role in drug formulation. Different types of Bhajana techniques include cooking, resting, and storing. resting is a process in which Kalaka/Kwatha of pharmaceuticals is leaved or applied to various metal surfaces in order to fortified the properties of that metal into that formulation. A review of Bhajana samskara, specifically using the Lepana or resting technique, has been completed, and the possible role of different metals on different formulations has been examined. For this, various Samhitas, ancient books and an online search for the Lepana technique have been reviewed. This is a unique formulation approach that should be standardized, and study should also be conducted with other specific metals that have health benefits.